Research on the Distribution Characteristics and Influencing Factors of Secondary Education Resources in Guangxi - Huang, Gaoqin; Shen, Yangdong (Asia Pacific Economic and Management Review, 2026)
Taking the Guangxi Zhuang Autonomous Region as a case study, this paper explores the spatial distribution pattern and influencing factors of secondary education resources. It comprehensively employs methods such as kernel density analysis, average nearest neighbor, spatial autocorrelation, and the location quotient model to characterize the spatial differentiation features of secondary education resources, and utilizes a ridge regression model to identify key factors influencing their distribution. The study finds that: (1) The distribution of secondary education resources exhibits an agglomeration pattern characterized by "dense in the southeast and sparse in the northwest"; (2) At the prefectural city scale, secondary education resources are clustered in their distribution, but the degree of clustering varies among cities; (3) At the county scale, the distribution of secondary education resources shows significant spatial heterogeneity, with notable disparities in allocation equity; (4) The spatial pattern of secondary education resources among counties is primarily shaped by six factors: year-end total population, registered (hukou) population, number of students enrolled in regular secondary schools, number of students enrolled in regular primary schools, balance of urban and rural household savings deposits, and number of industrial enterprises above a designated size. This reflects a multi-dimensional driving response of "basic demand—deferred planning—economic support." The research provides empirical evidence for understanding the issue of spatial equity of educational resources in border ethnic regions and holds reference significance for promoting the optimal allocation of educational resources and balanced regional development.